Optimasi Travelling Salesman Problem Pada Angkutan Sekolah Dengan Algoritme Particle Swarm Optimization - M. Khusnul Azhari; Imam Cholissodin; Fitra Abdurrachman Bachtiar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
Currently, The implementation of school transport has been done a lot of school, private and even the government. One of them is MI Salafiyah Kasim school. Although the school transport system has been implemented for years, there are obstacles such as students who are delivered not always the same every day, the driver delays in delivering to the destination, the school driver who always prioritizes personal experience and fund of transportation operations that are still unstable . To overcome these problems, the authors use the Particle Swarm Optimization Algorithm in the optimization to get the order of delivery of students with the shortest route that can be passed by the school driver. The results of this study compared actual sample data one day delivery with the system that has been designed. Of the five experiments applied to each kloter, three of them are able to produce a better route recommendation than the usual driver. Once reviewed overall, the system is considered to work well and produce a fairly optimal solution.